2021
DOI: 10.1186/s12917-021-02814-z
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin induces alpha-2u globulin nephropathy in male rats during diabetic kidney disease

Abstract: Background Alpha-2u globulin nephropathy mainly shows toxicological pathology only in male rats induced by certain chemicals and drugs, such as levamisole (antiparasitic and anticancer drugs). Streptozotocin (STZ) is also an anticancer-antibiotic agent that has been used for decades to induce a diabetic kidney disease model in rodents. The purpose of this study is to determine if STZ causes alpha-2u globulin nephropathy in male rats during an advanced stage of diabetic kidney disease. Alpha-2u … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A high level of activin A induces fibronectin production through the Smad signaling pathway with subsequent stimulation of tubulointerstitial fibrosis [ 55 , 56 ]. Furthermore, intracytoplasmic hyaline droplet deposition in the cells lining the renal tubules causes cellular degeneration with subsequent renal tubular degeneration and regeneration [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high level of activin A induces fibronectin production through the Smad signaling pathway with subsequent stimulation of tubulointerstitial fibrosis [ 55 , 56 ]. Furthermore, intracytoplasmic hyaline droplet deposition in the cells lining the renal tubules causes cellular degeneration with subsequent renal tubular degeneration and regeneration [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…To prove that G. spinigerum L3 could produce EVs, day 3cultured larvae were harvested and processed as described previously (17). Briefly, the larvae were fixed with 2.5% glutaraldehyde for at least 1 h, then washed 3 times for 10-15 minutes (min) each in sucrose phosphate buffer (SPB) pH 7.4.…”
Section: Examination Of Evs In G Spinigerum L3 By Temmentioning
confidence: 99%
“…The treatment with honey or propolis significantly restored the abnormal kidney function and proteinuria toward the normal range; the combination of honey and propolis showed a better protective effect. A recent study showed that STR causes alpha 2u-globulin nephropathy in > 80% of the moribund Wister male rats to manifest diabetic kidney injury within two weeks after STR injection [54]. It was found that hyperglycemia contributes to direct kidney damage, particularly in renal tubular cells [55].…”
Section: Effect Of the Intervention On Liver Enzymes Lipids And Hemog...mentioning
confidence: 99%